Problemy badawcze kultury organizacyjnej - wymiary i typologie - Mróz, Joanna (Research problems of organizational culture - dimensions and typologies, 2006)
The problem of description of organizational culture has been discussed in the paper. The typologies and the dimensions of organizational culture proposed by different authors have been compared. Both the typologies of organizational culture, based on two dimensions, and the multidimensional research approaches have been talked over. Finally the author’s own eight dimensional model of organizational culture has been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 32-41